Modulation of Motor Learning Capacity by Transcranial Alternating Current Stimulation. (1st November 2018) - Sugata, Hisato; Yagi, Kazuhiro; Yazawa, Shogo; Nagase, Yasunori; Tsuruta, Kazuhito; Ikeda, Takashi; Matsushita, Kojiro; Hara, Masayuki; Kawakami, Kenji; Kawakami, Keisuke
Highlights: Motor learning capacity significantly increased after 70-Hz tACS. Endogenous oscillatory beta activities were modulated after 70-Hz tACS. Changes in beta activity and improvement in motor learning were correlated. 70-Hz tACS may increase motor learning capacity by modulating beta activity. Abstract: Motor function can be modulated by transcranial alternating current stimulation (tACS) in alpha, beta, and high-gamma frequencies. However, few studies have investigated tACS-induced behavioral changes in combination with endogenous oscillatory neural activity in detail. Herein, we investigated the effect of tACS on motor learning capacity and endogenous oscillatory neural activity. Fifty-two healthy volunteers were randomly assigned to four stimulation groups (10 Hz, 20 Hz, 70 Hz, or sham) and performed a visually cued button press motor learning task before and after tACS, which was delivered at the left primary motor area. Oscillatory neural activities during the motor learning task were measured using magnetoencephalography (MEG). Following tACS, the capacity for motor learning was significantly increased for 70 Hz tACS compared to sham stimulation. Oscillation analysis revealed a significant increase in beta-band power after 70-Hz tACS but not in the other stimulation groups. Our finding that capacity for motor learning and endogenous oscillatory beta activity were modulated in parallel after 70-Hz tACS suggests that 70-Hz tACS may increase the motor learning capacity by cross-modulating beta oscillatory activity. Because high gamma and beta oscillatory activity have been shown to reflect the activity of excitatory and inhibitory interneuron, our results may derive from the modulation of excitatory and inhibitory interneurons in M1 by 70-Hz tACS.